Peran Otoritas Agama di Masa Pandemi Covid 19 - Parluhutan Siregar; Mara Ongku Hsb (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
The Covid-19 pandemic is a very dangerous virus that threatens various sectors of life including religious life and must follow health protocols, where usually open religious activities are carried out as widely as possible without any applicable rules like today, such religious activities are like conveying religious messages through virtual world, through zoom, google meet, religious education is delivered via virtual, as it should be. This study uses a library research method with a qualitative approach to obtain descriptive data on the results of religious research which plays a significant role in mitigating the epidemic and as a reactive force, religion is also a reactive and counter-productive force that contributes to spreading this epidemic through religious rituals. involving a large crowd. In Indonesia, religious authorities still play a significant role in a religious society. Religious authorities are actively responding to the Covid-19 pandemic in various ways. Various religious leaders, such as from the Indonesian Ulema Council (MUI), NU and Muhammadiyah, have responded to the Covid-19 pandemic.